21st Century Skills for Language Teaching and Learning - Ahmedova, Aziza (Журнал иностранных языков и лингвистики, 2021)
This paper discusses an innovative contribution of STEAM and Context-based learning to foreign language education and clarifies the national need for such an interdisciplinary education.Along the way,this paper is dedicated to solve the current problems connected with learning languages and subjects via distinct contemporary learning methods.